Primary renal magnesium wasting: an unusual clinical picture of exercise‐induced symptoms. Issue 8 (25th April 2016) - Stark, Christopher M.; Nylund, Cade M.; Gorman, Gregory H.; Lechner, Brent L.
Abstract: Magnesium is one of the most abundant cations in the human body and plays a key role as a metabolic enzyme cofactor and regulatory ion for neurons and cardiomyocytes. Hypomagnesemia due to isolated primary renal magnesium wasting is a rare clinical condition typically associated with neurological hyperexcitability. Exercise‐related gastrointestinal symptoms are caused by ischemic, mechanical, or neurohormonal changes. The role of hypomagnesemia in gastrointestinal symptoms is not well understood. We present a case of a 15‐year‐old male who presented with exercise‐induced abdominal pain, nausea, and vomiting, who was found to have profound hypomagnesemia and inappropriately elevated fractional excretion of magnesium (FEMg). Testing for multiple intrinsic and extrinsic etiologies of renal magnesium wasting was inconclusive. He was diagnosed with primary renal magnesium wasting and his symptoms resolved acutely with intravenous magnesium sulfate and with long‐term oral magnesium chloride. Primary renal magnesium wasting is a rare clinical entity that can cause extreme hypomagnesemia. It has not been associated previously with exercise‐induced gastrointestinal symptoms. The effects of hypomagnesemia on the human gastrointestinal tract are not well established. This case offers unique insights into the importance of magnesium homeostasis in the gastrointestinal tract. Exercise‐induced splanchnic hypoperfusion may contribute to gastrointestinal symptoms observed in this chronically hypomagnesemic patient. Abstract : This article presents the case of an adolescent male with exercise‐induced abdominal pain, nausea, and vomiting, that was found to have profound hypomagnesemia and inappropriately elevated fractional excretion of magnesium. He was diagnosed with primary renal magnesium wasting and his symptoms resolved acutely with intravenous magnesium sulfate and with long term oral magnesium chloride. This case represents the first report of exercise‐induced gastrointestinal symptoms related to hypomagnesemia and primary renal magnesium wasting, and highlights the importance of magnesium homeostasis in the gastrointestinal tract.